Improving community health through marketing exchanges: a participatory action research study on water, sanitation, and hygiene in three Melanesian countries - Barrington, Dani J.; Sridharan, Srinivas; Saunders, Stephen Graham; Souter, Regina T.; Bartram, Jamie K.; Shields, Katherine F.; Meo, Semisi; Kearton, Annika; Hughes, R. K. (Elsevier, 2016)
Diseases related to poor water, sanitation and hygiene (WaSH) are major causes of mortality and morbidity. While pursuing marketing approaches to WaSH to improve health outcomes is often narrowly associated with monetary exchange, marketing theory recognises four broad marketing exchange archetypes: market-based, non-market-based, command-based and culturally determined. This diversity reflects the need for parameters broader than monetary exchange when improving WaSH. This study applied a participatory action research process to investigate how impoverished communities in Melanesian urban and peri-urban informal settlements attempt to meet their WaSH needs through marketing exchange. Exchanges of all four archetypes were present, often in combination. Motivations for participating in the marketing exchanges were based on social relationships alongside WaSH needs, health aspirations and financial circumstances. By leveraging these motivations and pre-existing, self-determined marketing exchanges, WaSH practitioners may be able to foster WaSH marketing exchanges consistent with local context and capabilities, in turn improving community physical, mental and social health.
Keywords: PAR; Sanitation marketing; Pacific; Fiji; Solomon Islands; Vanuatu; Social capital; Well-being